2016
DOI: 10.3174/ajnr.a4771
|View full text |Cite
|
Sign up to set email alerts
|

Association of Automatically Quantified Total Blood Volume after Aneurysmal Subarachnoid Hemorrhage with Delayed Cerebral Ischemia

Abstract: BACKGROUND AND PURPOSE:The total amount of extravasated blood after aneurysmal subarachnoid hemorrhage, assessed with semiquantitative methods such as the modified Fisher and Hijdra scales, is known to be a predictor of delayed cerebral ischemia. However, prediction rates of delayed cerebral ischemia are moderate, which may be caused by the rough and observer-dependent blood volume estimation used in the prediction models. We therefore assessed the association between automatically quantified total blood volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 17 publications
2
27
0
1
Order By: Relevance
“…Thus, the possibility that the Hijdra score has a higher association to DCI as the Fisher and modified Fisher score cannot be ruled out. Recently, new radiological scales like the Barrow Neurological Institute SAH Grading Scale, incorporation of the Modified Graeb score to the modified Fisher, and quantification of SAH volume have been introduced [67,[68][69][70][71]. These scales measure the amount of blood in a more quantitative manner and have shown high associations with DCI and reduced interobserver variability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the possibility that the Hijdra score has a higher association to DCI as the Fisher and modified Fisher score cannot be ruled out. Recently, new radiological scales like the Barrow Neurological Institute SAH Grading Scale, incorporation of the Modified Graeb score to the modified Fisher, and quantification of SAH volume have been introduced [67,[68][69][70][71]. These scales measure the amount of blood in a more quantitative manner and have shown high associations with DCI and reduced interobserver variability.…”
Section: Discussionmentioning
confidence: 99%
“…Some image-derived features that are well known for being associated with DCI are the TBV and the blood location 3. The manual extraction of features from medical images is a time-consuming task and these features might not be the only important ones available in the images 21…”
Section: Methodsmentioning
confidence: 99%
“…The dataset is randomly split into training (75%) and testing (25%) set to prevent overoptimistic results. Model 1 included the following variables: WFNS, age, aneurysm treatment (clipping or coiling), intraparenchymal and intraventricular hemorrhage and TBV 3. Model 2 included the following variables: hypertension, diabetes mellitus, history of smoking, alcohol use, hyperglycemia and Hunt and Hess grade on admission 4…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found a strong relation between the quantified amount of total blood volume and DCI. 9,21 However, in these studies, the volumes of blood in the separate compartments of the brain were not analyzed separately. It is therefore currently unknown whether taking the blood volumes at these locations into account improves the prediction of DCI.…”
mentioning
confidence: 99%